Internet connectivity disruption in Argentina (Argentina) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Argentina. Data sourced from IODA.
Network Disruption Incident ID: AR-2026-0048. Severity: critical. Confidence: 75%